Price channel versus quantity channel: The relationship between government domestic borrowing from commercial banks and private sector credit in Kenya - Camilla Chebet; Samuel Kiemo (Kenya Bankers Association (KBA), 2017)
There has been a long standing debate on the effect of government domestic borrowing from commercial banks by increasing average lending rates, suggesting that increasing government spending financed by the banking sector crowds out private sector credit through price channel. However, empirical studies affirm that the price channel is not observed in developing economies due to financial frictions and financial repression as suggested by McKinnon (1973) and Shaw (1973). This paper aims to contribute to this debate by establishing the relationship between government domestic borrowing from commercial banks and private sector credit, identifying the channel of the crowding-in or crowding-out effect, estimating the magnitude and persistence of the crowding-in or crowding-out effect on private sector credit. The paper uses quarterly and monthly data to capture the dynamics of government borrowing and private sector credit from 1997- 2016, applying the Autoregressive Distributed Lag model (ARDL) and impulse response functions. The estimated model confirms that government domestic borrowing from the banking sector crowds out investment as every shilling lend to the government from the banking sector reduces private sector credit by 15 cents. Evidence affirms that crowding out is prevalent via the quantity channel where government borrowing competes with loanable funds that would otherwise be lend to the private sector. Consistent with popular empirical findings, the price channel though present is muted and impulse response functions confirm that crowding out via the quantity channel dissipates within two years. In addition, private sector credit is more stimulative of growth than government borrowing from the banking sector, though transient.
Keywords: 330